A Transcultural History of Art - Li, Jun. author. aut Link
V, 382 p. 325 illus., 281 illus. in color.
Keywords: This book unfolds the artistic and cultural exchanges between China, Persia, and Italy, picturing “a Transcultural Renaissance on the Silk Road” with fascinating reading of rich images. The author has been intensely engaged in the transcultural art history for more than a decade, spanning east and west, crossing different fields of painting, architecture, philosophy, cartography and literature. With illuminating case studies, it also explores the intermedial play between painting and poetry, poetry and architecture and visual art and literature. The book proposes "another form of history of art ": history of art is a theoretical history that interprets works of art; yet it is also a "visible history of art" that exists in the form of exhibitions.